Analysis of Lampung Export Value 2015-2023 with The Arima Method Approach (Autoregressive Integrated Moving Average) - Royiv Agmadeni (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
One indicator to see the economic development of a country is to look at the value of international trade or what is commonly referred to as export-import activities. This activity is one of the foreign exchanges for the country. Proper planning will increase this activity which will also have an impact on increasing the country's foreign exchange. To improve the welfare of the Indonesian people, one alternative is to increase the rate of economic activity in Indonesia, one of which is export activity. Increasing export activities is inseparable from the right economic strategy. The strategy can be formed by knowing the economic market conditions, namely by forecasting. One of the forecasting methods that can be applied is the Autoregressive Integrated Moving Average or ARIMA method. The best ARIMA model that fulfills is the ARIMA (2,1,0) model because of the smallest AIC value.